Effect of Two Work-to-Rest Ratios on Cardiovascular, Thermal, and Perceptual Responses During Fire Suppression and Recovery. (1st November 2016) - Hostler, David; Colburn, Deanna; Rittenberger, Jon C.; Reis, Steven E.
Abstract : Objective: Fire suppression is a physically demanding occupation that often results in significant heat stress and hypohydration. Guidelines for the number of work intervals allowed before a structured recovery were consensus derived and have not been tested.Methods: Apparently healthy firefighters were recruited for this field study. Subjects were assigned to two or three bouts of live fire training prior to 20 minutes of structured recovery to provide rehydration and cooling. After recovery, the subjects completed a timed test of firefighting skills.Results: Extending the fire suppression interval from two to three work periods before a structured recovery period increased core temperature and the time required to perform a high intensity circuit of firefighting skills immediately following recovery. A mild hypotension was noted during recovery but the groups did not differ for blood pressure, heart rate, or firefighter perception of thermal strain or exertion.Conclusions: This is the first study to examine the physiologic effects of structural firefighting work intervals on recovery and subsequent performance. Both groups experienced maximal cardiovascular strain during fire suppression but extending the work interval worsened heat stress and negatively affected certain aspects of performance immediately following the recovery period.